Maximizing light absorption and photocurrent in organic solar cells by aligning intrinsic absorption peaks with Fabry-Perot resonances - Ju, Seongcheol; Son, Ji Yeon; Kang, Taeyoung; Kwak, Hojae; Eun, Hyeong Ju; Lee, Ah Young; Kim, Jong H.; Lee, Kyu Tae (Optical Materials, 2024)
We provide a physical interpretation of the mechanism by which maximum light absorption is achieved in organic solar cells (OSCs) through the tailoring of Fabry-Perot (FP) resonances. Overlapping the intrinsic absorption peaks of the active layer with the FP resonances in a planar OSC structure maximizes light absorption, leading to the highest short-circuit current density (JSC). The OSC with a 119 nm-thick active layer of PTB7-Th:IEICO-4F, where intrinsic absorption peaks occur at wavelengths of 715 nm and 885 nm, exhibits fundamental FP resonant modes at wavelengths of 500, 715, 750, and 850 nm. The strong electric field intensity generated by the FP resonance coincides with the intrinsic absorption peaks of the active layer at 715 nm and 885 nm, leading to an experimentally observed JSC of 26.50 mA/cm2. Optical admittance analyses are conducted to investigate the reduced reflection associated with enhanced light absorption. These results provide a deeper understanding of the fundamental mechanism for designing multilayer photonic and optoelectronic devices. This design principle is general and can be applied to various optoelectronic devices, such as photovoltaics, sensors, and photodetectors across a wide range of wavelengths.
Keywords: Absorption peaks; Active Layer; Fabry-Perot resonances; Intrinsic absorptions; Optoelectronics devices; Organics; Photocurrent enhancement; Physical interpretation; Short circuit current density; Solar cell structures; Fabry-Perot resonance; Intrinsic absorption; Organic solar cell; Photocurrent enhancement